Penerapan Metode Bussines To Consumer (B2C) dalam Membangun Sistem Informasi Penjualan Bahan Pembersih Berbasis Web (Studi Kasus pada CCE Store) - Chandra, Yudi Irawan; Sjafrina, Fitri; Arnesia, Pipit Dewi (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
In building a web-based cleaning material sales information system, the Business to Consumer (B2C) method is applied with the aim of improving a more efficient and effective sales process and reaching a wider market. This research builds a web platform that facilitates direct communication between manufacturers or distributors of cleaning materials and end consumers. This system was created with the aim of providing easy access to product information, transparent pricing, and a simple transaction process. The process of developing this web-based information system involves a number of steps, starting from analyzing needs, designing the system, implementing the design to conducting trials and evaluations. During the needs analysis process, the functional and non-functional needs of the users, either those who produce or use the products, were recognized. The system design includes a user interface that is easy to understand, a database that is efficient in its structure, as well as crucial features such as product listing, shopping cart, online payment methods, and order monitoring. To carry out the implementation, the latest web technologies such as HTML, CSS, and JavaScript were used along with the Laravel framework on the backend side. Product, transaction, and user information were managed using a MySQL database. The system is tested as a whole to verify each feature operates effectively and according to predefined specifications. From this research, it is evident that applying the B2C method in a web-based cleaning material sales information system increases consumer satisfaction because it provides easier, faster, and safer access to information and transactions. In addition, this system also plays a role in helping manufacturers manage sales and inventory more efficiently, as well as presenting analytical data that is useful for business decision making. Overall, the web-based B2C cleaning sales information system solution provides innovation and practicality in supporting business operations in the digital age. Not only does this technology improve the efficiency of the sales process, it also opens up new opportunities in marketing and distributing cleaning products more broadly.